The Influence of Marketing on Instagram and Ewom Social Media on Purchase Decisions is Mediated by Brand Trust at Fore Coffee Ngagel Surabaya - Debora Hutabarat; Sri Tjondro Winarno; Nisa Hafi Idhoh Fitriana (Universitas Muhammadiyah Jakarta, 2025)
This study aims to analyze the impact of marketing through social media, Instagram, and Electronic Word of Mouth (EWOM) on purchasing decisions, considering the mediating roles of Brand image and Brand trust at the Fore Coffee branch in Ngagel, Surabaya. The method used in this research is quantitative with a survey approach, where the questionnaire is the primary data collection tool. The obtained data were analyzed using the Structural Equation Model (SEM) with the assistance of WarpPLS 7.0 software. The results indicate that Instagram and EWOM positively and significantly influence purchasing decisions directly and indirectly through Brand image and Brand trust. Instagram contributes 27.6% to purchasing decisions, while EWOM contributes 14.8%. Additionally, Brand image and Brand trust act as mediators in the influence of Instagram and EWOM on purchasing decisions, with contributions of 22% and 23.1%, respectively. This research provides practical implications for Fore Coffee in optimizing marketing strategies through Instagram and enhancing service quality to maintain customer satisfaction.